Curricular design for the career of economy of the secular university Eloy Alfaro of Manabí based in competitions - Robert Alfredo Pilozo-Cedeño (Universidad del Magdalena, 2016)
The author exposes the results of an investigation that looks for to solve the inadequacies that are manifested in the design of the curriculum of the Career of Economy of the Secular University Eloy Alfaro of Manabí (ULEAM), those that limit the acting of the graduate ones in function of the social demands toward economist's profession. A model of curricular design is contributed based on professional competitions. The methodology that allowed to apply the Pattern is sustained in a system focus where they are distinguished the subsystems of planning, execution and evaluation of the curriculum that allow to carry out the curricular design based on professional competitions in the career of Licentiate in Economy. Their general budgets admit their introduction in the practice, the evaluation of the impact and later generalization to other careers and universities of the country.